2018
DOI: 10.1111/cen.13588
|View full text |Cite
|
Sign up to set email alerts
|

Associations of insulin‐like growth factor‐I and insulin‐like growth factor binding protein‐3 with bone quality in the general adult population

Abstract: Our data suggest an important role of IGF-I on bone quality in men. The observed association of IGF-I with the QUS-based stiffness index and QUS-based fracture risk in this study might animate clinicians to refer patients with low IGF-I levels, particularly men, to a further evaluation of risk factors for osteoporosis and a detailed examination of the skeletal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Accordingly, lower protein intake leads to lower IGF-1 (25,27) which in turn leads to a lower bone mass (25)(26)(27)(28) . This could result in a higher fracture risk, with studies finding a negative association between IGF-1 concentration and predicted fracture risk (25,29,30) . Correcting low-protein intake theoretically leads to a variety of musculoskeletal health benefits in older individuals ( Fig.…”
Section: Anabolic Associations Of Dietary Protein With Bone Healthmentioning
confidence: 99%
“…Accordingly, lower protein intake leads to lower IGF-1 (25,27) which in turn leads to a lower bone mass (25)(26)(27)(28) . This could result in a higher fracture risk, with studies finding a negative association between IGF-1 concentration and predicted fracture risk (25,29,30) . Correcting low-protein intake theoretically leads to a variety of musculoskeletal health benefits in older individuals ( Fig.…”
Section: Anabolic Associations Of Dietary Protein With Bone Healthmentioning
confidence: 99%
“…Research by Misra et al[32] showed that patients with AN manifest elevated growth hormone (GH) and low IGF-1 concentrations, suggesting some degree of resistance to GH. Since IGF-1 exerts stimulatory effects on osteoblasts,[33] it has been postulated that the low IGF-1 in patients with AN may contribute to their low bone density. [2834] Later studies have confirmed an association between IGF-1 and BMD in patients with AN independent of their BMI.…”
Section: What Factors Contribute To An-related Bone Disease?mentioning
confidence: 99%
“…IGFBP-3 is a binding protein of IGF-I, which regulates the synthesis of IGF-I, prolongs the half-life of IGF-I in bone metabolism, regulates the metabolism of vitamin D, and promotes the utilization of calcium [6]. According to a study, circulating levels of IGF-I and IGFBP-3 were significantly lower in older adults than in the young population, and a low circulating IGF-I and IGFBP-3 level was associated with osteoporosis [7]. However, other researchers reported that IGFBP-3 is a potent inhibitor of IGF-Imedicated DNA synthesis [8], indicating that IGFBP-3 could counteract the physiological function of IGF-I to a certain extent.…”
Section: Introductionmentioning
confidence: 99%